Advancement of biorefinery-derived platform chemicals from macroalgae: a perspective for bioethanol and lactic acid - Tong, K.T.X. (Springer Science and Business Media Deutschland GmbH, 2022)
The extensive growth of energy and plastic demand has raised concerns over the depletion of fossil fuels. Moreover, the environmental conundrums worldwide integrated with global warming and improper plastic waste management have led to the development of sustainable and environmentally friendly biofuel (bioethanol) and biopolymer (lactic acid, LA) derived from biomass for fossil fuels replacement and biodegradable plastic production, respectively. However, the high production cost of bioethanol and LA had limited its industrial-scale production. This paper has comprehensively reviewed the potential and development of third-generation feedstock for bioethanol and LA production, including significant technological barriers to be overcome for potential commercialization purposes. Then, an insight into the state-of-the-art hydrolysis and fermentation technologies using macroalgae as feedstock is also deliberated in detail. Lastly, the sustainability aspect and perspective of macroalgae biomass are evaluated economically and environmentally using a developed cascading system associated with techno-economic analysis and life cycle assessment, which represent the highlights of this review paper. Furthermore, this review provides a conceivable picture of macroalgae-based bioethanol and lactic acid biorefinery and future research directions that can be served as an important guideline for scientists, policymakers, and industrial players. Graphical abstract: Figure not available: see fulltext.. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.